Study of oxygen separation from air - Tan, He Jiang (2019)
An increase in the demand for pure Nitrogen and Oxygen for a wide variety of applications provide the impetus towards the improvement of Pressure Swing Adsorption (PSA) gas separation technique as an alternative to the conventional cryogenic distillation procedure. Many studies have been done to effectively remove Nitrogen from the air, but the purity of Oxygen separated from similar processes are limited by the presence of Argon which is similar in characteristics as an adsorbate. An investigation into the development of PSA to further separate air into Nitrogen, Oxygen and Argon in high purity was done to contribute towards the advancement of their high-purity production process so that PSA air separation devices can be used in medical, production processes and military applications. The objectives are to identify the relative adsorption selectivity from isothermal adsorption equilibrium experiments from MIL-101(Cr) Metal-Organic Framework and AQSOA-Z02 Chabazite-Structured Zeolite with pure gases of Nitrogen, Oxygen and Argon; and develop a simulation tool using the experimental data to study and analyse the separation of air through PSA. It was found that the MIL-101(Cr) is only a good adsorbent for gas separation of Nitrogen and Argon at an elevated temperature of 320K. AQSOA-Z02 Chabazite was a more viable option for the gas separation of Argon from the other gas components at higher uptake levels which can be induced by having a high adsorption pressure. The favourable size of the Argon gas particles allowed it to diffuse further into the porous structure and adsorb more efficiently than the other larger gas molecules of Nitrogen and Oxygen. This is reflected by a higher relative adsorption equilibrium selectivity and kinetic selectivity.